Pornographic And Social Economic Exposure Affect The Age Of Menarch - Winda Nurmayani; Kusniyati Utami; Misroh Mulianingsih; Fitri Romadonika; BqRia Syafraini (Poltekkes Kemenkes Surakarta, 2021)
Background: Menarche is the first menstruation which occurs in middle age of adolescence before entering the reproductive period. Menarche can cause negative reactions in young women due to a lack of readiness and knowledge about personal hygine during menstruation, this is can cause of UTI (Urinary Tract Infection). Asserted that the factors that influence menarche were nutritional status, exposure to mass media and fast food consumption. Media exposure to adolescents will enhance many aspects related to the sexual maturation of the adolescences. Aim of study is to determine the pornographic exposure and economic status in students. Methods: A mix methods was match qualitative and quantitative research, the samples of the research used were 47 people, they were taken using purposive sampling technique. Results: The results of this research showed that the age of menarche which occurred were8 to 12 years old. Factors associated with the menarche were socioeconomic status (p-value 0.020) and exposure to pornography (p-value 0.037). Conclusion: Pornographic and socio economic status affect the age of menarchthe results can be used as material for consideration to provide early reproductive health education and supervise children in using cellphones and internet access.